Retinal accumulation of zeaxanthin, lutein, and β-carotene in mice deficient in carotenoid cleavage enzymes. (June 2017) - Li, Binxing; Vachali, Preejith P.; Shen, Zhengqing; Gorusupudi, Aruna; Nelson, Kelly; Besch, Brian M.; Bartschi, Alexis; Longo, Simone; Mattinson, Ty; Shihab, Saeed; Polyakov, Nikolay E.; Suntsova, Lyubov P.; et al.
Abstract: Carotenoid supplementation can prevent and reduce the risk of age-related macular degeneration (AMD) and other ocular disease, but until now, there has been no validated and well-characterized mouse model which can be employed to investigate the protective mechanism and relevant metabolism of retinal carotenoids. β-Carotene oxygenases 1 and 2 (BCO1 and BCO2) are the only two carotenoid cleavage enzymes found in animals. Mutations of the bco2 gene may cause accumulation of xanthophyll carotenoids in animal tissues, and BCO1 is involved in regulation of the intestinal absorption of carotenoids. To determine whether or not mice deficient in BCO1 and/or BCO2 can serve as a macular pigment mouse model, we investigated the retinal accumulation of carotenoids in these mice when fed with zeaxanthin, lutein, or β-carotene using an optimized carotenoid feeding method. HPLC analysis revealed that all three carotenoids were detected in sera, livers, retinal pigment epithelium (RPE)/choroids, and retinas of all of the mice, except that no carotenoid was detectable in the retinas of wild type (WT) mice. Significantly higher amounts of zeaxanthin and lutein accumulated in the retinas of BCO2 knockout ( bco2 -/- ) mice and BCO1/BCO2 double knockout ( bco1 -/- /bco2 -/- ) mice relative to BCO1 knockout ( bco1 -/- ) mice, while bco1 -/- mice preferred to take up β-carotene. The levels of zeaxanthin and lutein were higher than β-carotene levels in the bco1 -/- /bco2 -/- retina, consistent with preferential uptake of xanthophyll carotenoids by retina. Oxidative metabolites were detected in mice fed with lutein or zeaxanthin but not in mice fed with β-carotene. These results indicate that bco2 -/- and bco1 -/- /bco2 -/- mice could serve as reasonable non-primate models for macular pigment function in the vertebrate eye, while bco1 -/- mice may be more useful for studies related to β-carotene. Highlights: BCO1 and BCO2 regulate carotenoid delivery into the mouse retina. Zeaxanthin and lutein are preferentially accumulated in the mouse retina. Bco2 -/- mice can serve as "macular pigment mice" in study of eye disease prevention.